Prudência e Virtude Moral em Aristóteles. - Huppes, Daniel (2013)
This work aims to analyze the relationship between prudence and moral virtue in the Aristotle’s Nicomachean Ethics. The main research focus will be on the prudence issue: if the ownership of this intellectual virtue implies the possession of all the moral virtues or just some of them. By identifying that the main feature of prudence is good deliberation – of universals as well as of individuals – it is possible to affirm that the prudent is able to perform actions that are similar to the corresponding moral virtues. However, this is not the same as saying that he possesses all the moral virtues because, according to Aristotle, the acquisition of moral virtues depends on the repeated practice of virtuous actions.